She's a Boy I Knew - Haworth, Gwen (Haworth, Gwen, 2007)
Verzio FF Duration: 01:10:00 Filmmaker Gwen Haworth was born as Steven, the eldest of three children and the only son. From his early childhood, Steven thought of himself not as a boy, but a girl. He had nightmares in which he was rejected and abandoned, but he never spoke about his feelings and carefully kept his true identity hidden. In 2000, once he had already gotten married, he decided to come out to his family and go through with a sex change, starting with a new name and eventually undergoing hormone treatment and surgery. It was a lengthy and often arduous procedure, but ultimately Steven became Gwen. In She's a Boy I Knew, Gwen documents everything she went through in the years after her coming out. She interviews her parents, her two sisters, her wife and her best friend, who candidly explain how their initial confusion eventually changed into acceptance.